ON TWO AMPHISTOME CERCARIAE FROM DISTRICT MEERUT - PANDEY, K.C.; ., NEELAMPANWAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2000)
The present communication deals with a known and unknown amphistome cercariae from District Meerut. Cercaria baughi n.sp. was collected from Indoplanorbisexustus (Deshyaes) and characterized in having different shapes of eye spots, absence of crystalline lenses, presence of three genital rudiments and short intestinal caeca. Cercaria chauhani Pandey and Jain, 1971 is being redescribed from I. exustus as it shows minor variations. During the course of study of larval trematodes of District Meerut, we came across two and one snails of genus Indoplanorbisexustus infected with a new and an already known amphistome cercariae out of 120 snails examined at Meerut.